Rituximab-based treatments followed by adoptive cellular immunotherapy for biopsy-proven EBV-associated post-transplant lymphoproliferative disease in recipients of allogeneic hematopoietic stem cell transplantation. (3rd May 2016) - Jiang, Xinmiao; Xu, Lanping; Zhang, Yu; Huang, Fen; Liu, Daihong; Sun, Jin; Song, Chaoyang; Liang, Xinquan; Fan, Zhiping; Zhou, Hongsheng; Dai, Min; Liu, Can; et al.
ABSTRACT: To improve prognosis of post-transplant lymphoproliferative disease (PTLD), a sequential therapeutic strategy that rituximab-based treatments followed by donor lymphocyte infusion (DLI) or autologous EBV-specific cytotoxic T lymphocytes (EBV-CTL) for biopsy-proven EBV-associated PTLD in recipients of allogeneic hematopoietic stem cell transplantation was designed. 84 patients with EBV-PTLD were enrolled in this prospective study. After two cycles of the rituximab-based treatments, 68 of 84 patients (81% [95% CI 71–88]) responded and 52 (62% [51–72]) had CRs. This increased to 73 of 77 patients (95% [87–98]) with completion of sequential cell infusions, and 70 of 77 (91% [82–96]) achieved CRs after DLI or autologous EBV-CTL infusion. 22 patients experienced acute GVHD (aGVHD) (grade I in 5 and grade II in 13, grade III in 4) and 13 chronic GVHD (limited cGVHD in 7 and extensive cGVHD in 6) in 62 patients undergoing a median of three doses of DLI. The incidences of GVHD were similar between DLI and EBV-CTL group (aGVHD 35% vs. 33%, p = 0.876; cGVHD 21% vs. 13%; p = 0.503). EBV-CTL activity after the rituximab-based treatments did not change, while increased after cell infusions and reached its maximum in the 3rd or 6th month after EBV-CTL or DLI treatment, respectively. The 5-y cumulative incidence of PTLD relapse was 4.5% ± 3.3%. The 5-y overall survival (OS) and progression-free survival (PFS) after PTLD were 70.7% ± 5.2% and 68.9% ± 5.3%, respectively. Rituximab-based treatments combined with adoptive cellular immunotherapy might elevate CR rates and reduce relapse of PTLD after allo-HSCT.